Correlation of qSOFA and NLR to Procalcitonin Levels for Predicting Outcome of Pneumonia Sepsis Patients at RSUP dr. M. Djamil Padang - Ibnu Arief Dafitri; Oea Khairsyaf; Irvan Medison; Yessy S. Sabri (Jurnal Respirologi Indonesia, 2020)
Backgrounds: Sepsis is a common complication that occurs due to infection and can increase morbidity and mortality in patients. Several methods are applied to evaluate the prognosis of sepsis, such as quick Sequential Organ Failure Assesment (qSOFA) score, Neutrophil Lymphocyte Ratio (NLR) and procalcitonin. This study aimed to determine correlation of qSOFA and NLR on procalcitonin levels to predict the outcome of pneumonia sepsis patients in the pulmonary ward of RSUP dr. M. Djamil Padang. Methods: This was a cross sectional study of pneumonia sepsis patients in the pulmonary ward of the RSUP dr. M. Djamil Padang during September 2019 - February 2020. The qSOFA score was assessed based on physical examination, while both NLR and procalcitonin were measured from blood tests. Results: There was a significant relationship between qSOFA score and procalcitonin levels (r=0.409; P=0.006). There were no significant correlation between NLR and procalcitonin levels (r=0.232; P=0.134). There was a significant correlation between qSOFA score and patient outcome (P=0.036), there was no significant relationships between procalcitonin levels and patient outcomes (P=0.249), and there were no significant correlation between NLR and patient outcomes (P=0.157). Conclusions: qSOFA score was more considered method to evaluate the outcome of pneumonia sepsis patients. (J Respir Indo. 2020; 40(3): 173-81)